PENGARUH PENDEKATAN BERMAIN TERHADAP KETERAMPILAN SEPAK SILA - Saputra, Andi; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivated by the lack of soccer skills in the game of sepak takraw, showing that students' skills in doing soccer are less than optimal, lacking in soccer techniques. This study aims to learn how to learn the game of football in soccer extracurricular participants at SMA Negeri 1 Meliau. Research is an experimental study. The method used is